Impressões Pessoais do Dr. Wilson Barbosa Martins a respeito da política no sul de Mato Grosso entre as décadas de 1930 e 1960 - Silva Ferreira, Bruno Torquato; Hanemann, Marcos (Albuquerque (online), 2017)
.